2009
DOI: 10.1097/pec.0b013e318196ea6e
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Management of Pediatric Convulsive Status Epilepticus

Abstract: Convulsive status epilepticus is an important neurological emergency, with many children experiencing prolonged seizures in both the prehospital and hospital phases. Persistent seizure activity beyond 40 minutes contrasts with current published guidelines. There is a need to adopt a widely accepted approach to the management of children who fail to respond to standard anticonvulsant therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 25 publications
4
60
0
Order By: Relevance
“…The assessment of compliance and effectiveness was based on pre-existing and proposed quality assessment indicators for the treatment of pediatric SE that were discussed by experts at a Pediatric Emergency National Advisory Panel held in 2011 (Table 1). [24][25][26][27][28][29][30][31][32] Respiratory depression and hypotension, the two main serious adverse effects following the treatment of SE with benzodiazepines, 20 were used as the two safety outcomes. Respiratory depression was defined as any patient requiring bag/mask ventilation, continuous positive airway pressure (CPAP), or intubation.…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of compliance and effectiveness was based on pre-existing and proposed quality assessment indicators for the treatment of pediatric SE that were discussed by experts at a Pediatric Emergency National Advisory Panel held in 2011 (Table 1). [24][25][26][27][28][29][30][31][32] Respiratory depression and hypotension, the two main serious adverse effects following the treatment of SE with benzodiazepines, 20 were used as the two safety outcomes. Respiratory depression was defined as any patient requiring bag/mask ventilation, continuous positive airway pressure (CPAP), or intubation.…”
Section: Methodsmentioning
confidence: 99%
“…26 In a retrospective multicenter study of 542 episodes of convulsive seizures of 10 or more minutes duration in children, the median (p 25 -p 75 ) time from hospital arrival until administration of a non-BZD AED was 24 (15-36) minutes. 27 In a series of 199 children with febrile status epilepticus, the median time from seizure onset to administration of the first AED was 30 minutes. 28 The limited information reported on time of AED administration in adults also points towards significant delays in drug administration.…”
Section: (79)mentioning
confidence: 99%
“…17 In a series of 542 patients with convulsive seizures of at least 10 minutes duration, the median (p 25 -p 75 ) time from hospital arrival to administration of a non-BZD AED was 24 (15-36) minutes. 18 The study with the initial 81 patients in the pSERG consortium showed that the time elapsed since SE onset to administration of the first, second, and third AEDs were 28 (6-67) minutes, 40 (20-85) minutes, and 59 (30-120) minutes, respectively. 19 Different endpoints and methodologies complicate direct comparisons, but together, these data suggest that the timeliness of SE treatment needs improvement.…”
mentioning
confidence: 99%
“…Both adults [13][14][15][16][17] and children [17][18][19][20] receive antiepileptic drugs (AEDs) later than recommended by most SE guidelines. [21][22][23] Most episodes of pediatric SE occur in children with no history of seizures.…”
mentioning
confidence: 99%